High granulocyte-macrophage colony stimulating factor to interleukin 10 ratio and marked antioxidant enzyme activities predominate in symptomatic cattle naturally infected with Candidatus Mycoplasma haemobos, Theileria orientalis, Theileria sinensis and Trypanosoma evansi - Agina, Onyinyechukwu Ada; Cheah, Kim Tho; Ahmad Sayuti, Nurul Syahirah; Shaari, Mohd Rosly; Isa, Nur Mahiza Md; Ajat, Mokrish; Zamri-Saad, Mohd; Mazlan, Mazlina; Hamzah, Hazilawati (MDPI AG, 2021)
The aim of this study was to measure the serum proinflammatory (IL-12, GM-CSF & IFN-γ) to anti-inflammatory (IL-10, IL-4) cytokine ratio, oxidant (MDA) level and antioxidant enzyme (SOD; GPx) activities after blood parasite infections. The blood and serum samples were obtained from 130 cattle and screened for identity of the infecting blood parasites by conventional PCR. The following blood parasite species were detected: Candidatus Mycoplasma haemobos (70/130); Theileria orientalis (65/130); Theileria sinensis (32/130); Anaplasma marginale (49/130); Anaplasma platys (7/130); and Trypanosoma evansi (4/130). The GM-CSF/IL-10 ratio showed significantly higher values in all the symptomatic blood parasite infected cattle groups except for symptomatic A. platys infected cattle groups. Anti-inflammatory cytokine immune responses were notable findings in symptomatic and asymptomatic cattle infected with C. M. haemobos and T. orientalis characterized by low serum IL-12:IL-10, IFN-γ:IL-10, IL-12:IL-4 and IFN-γ:IL-4 (p < 0.05). Therefore, high serum GM-CSF:IL:10 in the symptomatic blood parasite infected cattle, low serum IL-12:IL-10, IFN-γ:IL-10, IL-12:IL-4 and IFN-γ:IL-4 ratios in asymptomatic cattle, high MDA level, and increased antioxidant enzyme activities could be useful predictive tools for outcome of natural blood parasite infections in cattle.